Barriers and facilitators in the inclusion of persons with disabilities in higher education: The students’ point of view - Wuo, Andrea Soares; Paganelli, Bruna Tamara Suzane (Education Policy Analysis Archives, 2022)
This article aims to identify the barriers and facilitating factors related to the inclusion process of persons with disabilities in higher education, from the point of view of students who experience this reality. To achieve the objective, bibliographic research and semi-structured interviews were conducted with two students enrolled in a public higher education institution in the city of Blumenau-SC. The bibliographic survey in the databases of the Coordination for the Improvement of Higher Education Personnel (CAPES), the Digital Bank for Theses and Dissertations (BDTD) and ScIELO (Scientific Electronic Library Online) resulted in 25 researches. The results were analyzed through content analysis and indicated that, both in the literature and in the interviews, the architectural, pedagogical, technological or attitudinal barriers are more evident than accessibility, which is still emerging in the higher education institution that was the setting for this research as well as universities in general, according to the analyzed literature.